Pengaruh Keberadaan Desa Wisata terhadap Kondisi Sosial dan Lingkungan Masyarakat : (Studi di Desa Gubugklakah Kecamatan Poncokusumo, Kabupaten Malang) - Rudy Catur Rohman Kusmayadi; Ahmad Fauzi (LP3M IAI Al-Qolam Malang, 2020)
All regions in Indonesia have the potential of a unique tourism village and become a tourist attraction. Therefore, encouraging the tourism sector becomes the right choice for the region to advance the economy. The village that has taken advantage of these bureaucracy opportunities in the tourism sector is Gubugklakah Tourism Village, Poncokusumo District, Malang Regency. Indeed it has both positive and negative impacts on the environment and socio-economic conditions of the community. This research was conducted with a qualitative approach to explore how the Existence of Tourism Village Affects Social and Environmental Conditions of Communities in Gubugklakah Village, Poncokusumo District, Malang Regency. The development of agriculture-based tourism in the village of Gubugklakah has a positive influence on the Gubugklakah community, especially on environmental and social aspects. In the environmental aspect, it increases recognition to protect the environment with an eco-friendly lifestyle. The structure development of tourism facilities that are not too conflicting with the local community's natural environment and socio-cultural has caused no pollution of the landscape in the village of Gubugklakah. The development of natural resources that are non-extractive, non-consumptive, and sustainable in tourism helps to lessen the negative impact. Moreover, the local community's role in social activities increases the sustainability of tourism activities in Gubugklah Village.. Keywords: Tourism Village, Community's Social Economic Condition.